Dekonstruksi Perlakuan Akuntansi Dana Syirkah Temporer: Jebakan Hibriditas Dan Hegemoni Paradigma Utang-Ekuitas Konvension - Rakhmawan Habibi; Mohamad Nur Husen; Abdul Wakhid; Ahmad Zainul Abidin (Islamic Banking and Finance, 2026)
Temporary Syirkah Funds in Islamic banking present a fundamental anomaly to conventional accounting architecture. This study employs a Derridean deconstruction approach to unravel the metaphysical assumptions underlying the current accounting treatment of DST, which places it in a "hybrid" position between debt and equity. The study's central argument is that this hybrid position is not an epistemological solution, but rather a compromise imposed by the dominance of the debt-equity dichotomous paradigm rooted in capitalist accounting ontology. This compromise effectively "tames" and obscures the unique essence of DST as a partnership contract based on profit and risk sharing. Through deconstructive analysis, this study demonstrates how this "in-between" position actually reinforces a hierarchy in which certainty and ownership are privileged over partnership .his research does not offer a reclassification, but rather proposes a radical shift: removing the DST from the conventional balance sheet framework and representing it in a new, performative primary report, the Partnership and Risk Sharing Report. This finding challenges standard setters to fundamentally rethink the architecture of Islamic financial reporting to make it more authentic to its philosophical principles.